FASTEATS: APLIKASI PEMESANAN MAKANAN BERBASIS ANDROID MENGGUNAKAN METODE PROTOTYPE - Alda, Muhammad; Praja, Andika; Maharani, Annisa; Sanjaya, Bima; Galasca, Syafhira Ananda (Smart Education, 2025)
Abstract: The increasing use of android applications makes all activities run more efficiently using android applications. The need for an efficient and practical food ordering system is increasing, especially in the digital age as it is today. This research aims to build an android-based food ordering application that is built in the hope of providing convenience to the public in ordering food according to their wishes as well as helping the development of MSME businesses. The research method used is qualitative method, which includes data collection through interviews and observations, then reinforced by literature studies. This study also used prototype methods as a framework for developing systems. The prototype method was chosen because it allowed iterative development of the system by actively engaging user feedback in each development stage. The result of this study was an application called